ЗНИЖЕННЯ ДИНАМІЧНИХ ВТРАТ В АКТИВНОМУ ОДНОФАЗНОМУ ЧОТИРИКВАДРАНТНОМУ ПЕРЕТВОРЮВАЧІ З ПОКРАЩЕНИМ АЛГОРИТМОМ ГІСТЕРЕЗИСНОЇ МОДУЛЯЦІЇ - Плахтій, О.А.; Нерубацький, В.П.; Сушко, Д.Л.; Кавун, В.Е. (Інститут електродинаміки Національної академії наук України, 2018)
Diodes and thyristor rectifiers used in traction drives of electric traction (EMF) alternatives are obsolete and require modernization. At the same time, it is promising to use in traction drives the active four-quadrant voltages rectifier. The advantage of which is the ability to implement a unity power factor, the formation of an sinusoid input current, and also the implementation of the mode of energy recovery into the power grid. Hysteresis control systems have been widely used for active four-quadrant converters. However, the lack of hysteresis modulation in active rectifiers is the need to implement a variable and a fairly high switching frequency in power switches: from kHz to tens of kHz. . The paper proposes an improved hysteresis control system, which allows to reduce dynamic losses in power convertor up to 33%. Proposed theoretical positions are confirmed by the results of simulation performed in the Matlab. References 16, figures 6, table 3.